Influence of network structures of nitrile rubbers on their thermal properties - Rybiński, P.; Janowska, G. (Polimery, 2009)
The results of investigations of the effects of network structures of butadiene-acrylonitrile rubbers (NBR18 and NBR39) on their thermal properties are presented. The rubbers were conventionally crosslinked with use of either dicumyl peroxide or sulfur, or unconventially, with iodoform (CHI3). The vulcanizates were characterized by derivatography (in an air atmosphere, Fig. 1-3, 5, 6 and 10, Table 1, 2), differential scanning calorimetry (DSC - in an inert gas atmosphere, Fig. 7, 12, Table 3) as well as by IR spectroscopy (Fig. 4, 6, 9, 11). It was demonstrated that iodoform vulcanizates showed the smallest decomposition rates and clearly higher glass transition temperatures, in comparison with conventionally crosslinked ones. It results probably from increasing mutual interactions of macromolecules, caused by modification with iodoform or with the products of its decomposition.